Análise crítica da especial situação do desconhecimento da lei a partir do estudo da evolução doutrinária da falta de consciência da ilicitude no Brasil - Brito, Nayara Graciela Sales (2012)
The scope of this study is to examine the ignorance of the law issue beginning with a historical study of criminal liability and mistake, moving on to the birth of culpability theories and the approaches to the knowledge of unlawfulness. This study addresses the development of culpability and mistake of law in Brazil, mainly through the study of Brazilian criminal statutes and bills. To this end, this study shows the development of the theory around the object of the knowledge of unlawfulness, and the prevailing opinions of Brazilian jurists in the sense of considering it to be in opposition to the established order of the community. This study is justified by the complexity and importance of the topic, both to crime theory and legal pragmatics, especially when one considers the numerous statutes enacted in Brazil, many of which date from the post-industrial period, as a means of keeping up with the risks posed by a global and technological society. The theoretical framework follows the historical and chronological line, and is not intended to exhaust the approaches to the subject nor is it aimed at offering solutions to all the lines of thought herein mentioned. This study covers different conceptions of culpability: psychological, normative, finalist, and the functional views of Claus Roxin and Günther Jakobs. Next, formal, material and intermediary theories of the object of the knowledge of unlawfulness is addressed in order to attain a critical view of inexcusable nature of the ignorance of the law defense in the face of the dignity of the human person